ANALISIS KASUS UJARAN KEBENCIAN BERDASAR SARA OLEH FERDINAND HUTAHAEAN: KAJIAN LINGUISTIK FORENSIK - Azizah, Nurul (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2024)
Abstract: This study aims to reveal forensic linguistic analysis using semantic theory from the Ferdinand Hutahean case in the form of a tweet upload that caused trouble in the community. This type of research is qualitative descriptive research. The research step is divided into three stages, namely data collection, data analysis, and presentation of the results of data analysis. Data collection is carried out by refer method and note technique. Data analysis uses distributional methods, while the presentation of data analysis results uses informal methods. Research results in conclusions that based on the analysis of lexical and grammatical meaning Tweet FH presents the meaning of comparison by mentioning the contrast of the differences in ‘my God’ and ‘your God’. He confirmed both with the opposite nature. According to him, your God is weak and needs to be defended, while Allah is extraordinary, all of everything and he puts my God as his appointment. FH also conveyed his satire to certain parties who carried out acts of defense against God. Tweet FH has the potential to cause trouble in the community, especially among Muslims and is related to SARA elements. In terms of legal responsibility, Tweet FH is related to ‘Pasal 14 ayat (1) Undang-Undang Nomor 1 Tahun 1946 tentang Peraturan Hukum Pidana’.Keywords: Linguistics, Semantic Analysis, Ferdinand Hutahaean Cases